Istikhdām al-Kumbiyūtir fī Taʼlīm al-Qurʻān al-Karīm - Ahmad Sayuthi Nasution (Al-Zahra : Journal for Islamic and Arabic Studies, 2006)
Computer is the science and technology progress. One of the modern methode quranic teaching is using computer. This article discribe modern methode quranic teaching.